2011
DOI: 10.1080/15381501.2011.549068
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Knowledge and Prevention Programming in Domestic Violence Shelters: How Are We Doing?

Abstract: Domestic violence shelters (n ¼ 59) in two southwestern states were surveyed about their services related to HIV prevention. Variables included organizational characteristics, agency protocols and practices, HIV=AIDS prevention programming, staffs' HIV=AIDS knowledge, and staffs' attitudes regarding HIV=AIDS prevention for women exposed to intimate partner violence. In this exploratory, descriptive study results indicated that most shelters had a significant awareness of how HIV=AIDS is transmitted, but few sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 24 publications
5
15
0
Order By: Relevance
“…Ninety-two percent of the DV shelter workers reported that HIV prevention interventions had never been implemented at their shelter and educational brochures about HIV prevention were rarely provided to residents. These findings are consistent with other reports that DV shelters are underutilized in HIV prevention (Rountree et al, 2011; Rountree et al, 2008). …”
Section: Discussionsupporting
confidence: 93%
“…Ninety-two percent of the DV shelter workers reported that HIV prevention interventions had never been implemented at their shelter and educational brochures about HIV prevention were rarely provided to residents. These findings are consistent with other reports that DV shelters are underutilized in HIV prevention (Rountree et al, 2011; Rountree et al, 2008). …”
Section: Discussionsupporting
confidence: 93%
“…Shelter residents also reported high levels of satisfaction with the intervention. These findings further support that women perceive shelters as a safe and protective environment for HIV testing and risk prevention (Cavanaugh et al, 2016; Rountree et al, 2011). …”
Section: Discussionsupporting
confidence: 71%
“…Women in shelters have already initiated a change in their life, and BWS provide a confidential, safe, supportive, and resource rich environment where women can safely obtain test results, cope, and access treatment if HIV positive (Rountree, Goldback, Bent-Goodley, & Bagwell, 2011). However, in a study of 59 BWS, 54% did not disseminate HIV information to residents and only 17% offered testing or sexual safety planning (Rountree et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43][44] However, the best practices for implementing a continuous universal IPV screening protocol within a HIV clinical care setting has not yet been fully developed.…”
Section: Introductionmentioning
confidence: 99%